ТЕОРЕТИКО-МЕТОДИЧНІ АСПЕКТИ ПІДГОТОВКИ СТУДЕНТІВ ДО ДІАГНОСТИКИ ВІКОВИХ ОСОБЛИВОСТЕЙ ПСИХІЧНОГО РОЗВИТКУ ДІТЕЙ (Modern Information Technologies and Innovation Methodologies of Education in Professional Training Methodology Theory Experience Problems, 2013)
The article is concerned with the theoretical and methodological aspects of students’ training for diagnostic the age features of children’s mental development.